Samples of creative individuals on the Kazakhstan stage (Journal of Philosophy Culture and Political Science, 2016)
This article discusses the performed plays on the theme of creative people on the stage of the Kazakh State academic drama theatre named after M.Auezov and the author has analyzed directing solutions and acting skills in the several plays as: “Gypsyserenade” by I. Saparbay, “Poet, angel, love” by A. Tarazi and “Actress” by D. Isabekov
Keywords: theatre; work; play; director; actor